Genetic determinants excluding GBCR::ABL mutations of imatinib mesylate therapy response among chronic myeloid leukaemia patients in Malaysia - Ismail, Siti Mariam (2023)
Despite imatinib mesylate (IM) being the frontline drug for successful treatment of chronic myeloid leukaemia (CML), a significant proportion of CML patients on IM therapy develop resistance and attain poor outcome. The objective of the present study was to investigate the contribution of selected polymorphisms of VEGFA (+936 C>T and -634 G>C), VEGFR2 (1192 C>T, ivs25-29 G>A and 1416 T>A), BIM (intron 2 deletion and c465 C>T), TP53 mutation at exon 8 and additional chromosome abnormalities (ACAs) in modulating IM treatment response and disease progression in 249 Malaysia CML patients undergoing IM treatemnt. For this study, CML patients comprising of 127 IM resistant and 122 IM good response were recriuted. For VEGFA +936 C>T and -634 G>C, VEGFR2 1192 C>T, ivs25-29 G>A and 1416 T>A and BIM c465 C>T Polymerase Chain Reaction- Restriction Enzyme Fragment Length Polymorphims (PCR – RFLP) was employed and allele specific – PCR (AS – PCR) for BIM intron 2 deletion polymorphims, TP53 mutation at exon 8 was investigated using PCR amplification followed by DNA sequencing. ACAs were investigated employing standard cytogenetic procedures and FISH. With regard to VEGFA, both the SNPs +936 C>T and -634 G>C showed significant lower risk for the development of resistance. For the homozygous variant (TT) +936 C>T, of showed OR: 0.11 (95 % CI = 0.02 – 0.56, p = 0.008) and CC of the -634 G>C showed OR: 0.17 (95 % CI = 0.07 – 0.41, p = 0.001). The C allele of -634 G>C was also significantly associated with lower risk for development of IM resistance (OR: 0.49, 95 % CI = 0.34 – 0.71, p = 0.001). In the case of VEGFR2, ivs25-29 G>A SNP, only homozygous variant (AA) showed significant lower risk association with development of resistance with OR, 0.17 (95 % CI = 0.04 – 0.84, p = 0.029). For SNP of 1416 T>A, the heterozygous variant (TA) and homozygous variant (AA) showed significant lower risk for development of resistance (OR: 0.25, 95 % CI: 0.11 – 0.59, p = 0.002 for heterozygous variant and OR: 0.27, 95 % CI = 0.12 – 0.62, p = 0.002 for homozygous variant respectively). In the case of TP53 exon 8 and BIM intron 2 deletion, all study subjects showed wildtype genotype with no mutation in exon 8 and no deletion detected in intron 2. For BIM c465 C>T, the heterozygous variant (CT) and dominant genetic model CT + TT (OR: 2.14, 95 % CI = 1.24 – 3.67, p = 0.006 and OR: 1.99, 95 % CI = 1.19 – 3.34, p = 0.009) and variant allele T (OR: 1.57, 95 % CI = 1.03 – 2.39, p = 0.036) showed higher risk for the development of resistance to IM. ACAs were detected in 40/ 249 patients (16.1 %). For determining the prognosis impact of ACAs, these 40 patients were categorized to those with Ph+/ ACAs and Ph-/ ACAs and further stratified into four groups based on the type of abnormalities. Patients with group 1 and group 2 abnormalities showed comparatively better prognosis while patients with group 3 and 4 abnormalities showed higher risk for disease progression. Novel ACAs consisting of rearrangements involving chromosomes 11 and 12 were found to lead to myeloid BP. Stratification based on individual ACAs found to have differential prognostic impact and might be a potential risk predictive system to prognosticate and guide treatment of CML patients. These findings from the present study demonstrated obvious relationships of host genetic and tumour genomic factors with IM treatment response and disease progression These genetic factors could be potential biomarkers to predict IM treatment response and disease progression in Malaysian CML patients.